Trend in 167 cases of minors witnessing violence: The role played by COVID-19 pandemic - Focardi, Martina; Grassi, Simone; Raddi, Silvia; Rosati, Maria Elena; Cazzato, Francesca; D’Onofrio, Paola; Doretti, Vittoria; Bianchi, Ilenia; Vetrugno, Giuseppe; Oliva, Antonio; Pinchi, Vilma (Frontiers in Pediatrics, 2022)
Background: There currently is no evidence that COVID-19 has had an impact on the rates of psychological abuses occurring when a minor witnesses interpersonal violence. Aim: Our aim was to describe the accesses of the last four years to the Emergency Department of a tertiary hospital (Careggi University Hospital - Florence, Italy) due to this issue and then to evaluate whether the COVID-19 has had an impact on this trend. Methods: We collected data regarding cases of abuse in which at least a minor had reportedly witnessed the event. Medical records stored between January 1, 2018 to January 1, 2022 were analyzed, extracting sex, age and nationality of the victim; sex of the perpetrator and relationship with the victim; known previous episodes of abuse in the medical history of the victim; setting of the abuse (domestic vs non-domestic); type of abuse (physical, psychological, sexual); whether the perpetrator was under the influence of alcohol/drugs; whether the victim was hospitalized; prognosis of the victim; number, relation with the victim and involvement in the abuse (as co-victim) of the minor(s) who witnessed the abuse. Results: A total of 167 eligible cases were registered. 69% of victims had previous episodes of abuse. The perpetrators were all known and mainly males (96%).The abuses were mainly domestic (79%). In 74% of the cases only a type of violence was perpetrated. In 12% of the cases, the minors were also victims of physical abuse. No statistically significant relationships were found between the start of the COVID-19 pandemic and the changes in the number of cases of domestic abuse (p = 0.07), physical abuse (p = 0.62), psychological abuse (p = 0.83) or sexual abuse (p = 0.88). However, during the institutional lockdown in Italy (March-May 2022) only two cases occurred – a number that did not allow period-specific statistical inference. Conclusions: Empowering the hospital policies specifically aimed at identifying and protecting the victims of violence/witnessed violence remains a critical goal from both a public health and medico-legal point of view.